PROCES „INKI” W ŚWIETLE ÓWCZESNEGO PRAWA - Olczyk, Małgorzata; Król, Mateusz (Civitas et Lex, 2017)
Danuta „Inka” Siedzik was a nurse. During the Second World War she belonged to the Home Army and to the independence organizations, which fighted with communist rule after the war. She was sentenced to death penalty and shot in jail in Gdańsk at the age of 17 for her service and fight. She belongs to cursed soldiers, that means activists of anti-communist underground. Although she died in 1946, her memory has been cultivated only for a dozen or so years. The aim of the article was an analyze of documents and interpret of legal regulations, which applied to Inka’ case. In the article compared content of the documents with regulations and that time. No moral judgment was made on the court’s decision, but were presented only the facts.